HUBUNGAN JENJANG PENDIDIKAN KEDISIPLINAN DAN KEGAIRAHAN KERJA DENGAN KINERJA KARYAWAN PADA SENTRA INDUSTRI SANGKAR BURUNG DI DESA DEBEGAN JEBRES SURAKARTA - Mrihrahayu R Mrihrahayu R (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2016)
The purpose of this study was (1) to measure and examine the relationship education, work discipline and work excitement with employee performance on an industrial district in the village Birdcage Debegan Jebres District of Surakarta. (2) To determine the factors that have the strongest association with the performance of employees in the industrial center of the Birdcage Village Debegan Jebres District of Surakarta. This study takes the object to the industrial centers in the village Birdcage Debegan Jebres District of Surakarta. The population in this study were employees in the industrial centers in the village Birdcage Debegan by 87 craftsmen with the number of workers / employees approximately 783 people. Determination of the number of samples taken is determined by the formula Slovin as many as 89 respondents by random sampling method. Data analysis technique using multiple correlation. The results of data analysis found that the variable levels of education, work discipline, and the excitement of work, had a significant relationship primarily to employee performance. Variable excitement of working has the strongest links to employee performance.